Risk Factors for Keratoconus Progression in Children Compared with Young and Middle-aged Adults - Sideroudi, Haris; Flockerzi, Elias; Jullien, Theresia; Hamon, Loïc; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2023)
Background To investigate the risk factors for keratoconus progression in children (10 – 18 years old; age group 1) compared to young adults (19 – 35 years old; age group 2) and middle-aged adults (36 – 55 years old; age group 3).Patients/Methods Ninety-seven children, 445 young adults, and 342 middle-aged adults underwent total ophthalmic examination including clinical refraction, slit lamp examination, corneal tomography, eye biometry, and biomechanical properties measurements. Comparisons were assessed among three age groups and between progressive and nonprogressive eyes. Logistic regression was applied to determine the potential prognostic factors for keratoconus progression in the three age groups.Results Univariate logistic regression analysis show that the most prominent factors associated with progression were corneal posterior vertical radius (RVP), eye rubbing (RUB), slit lamp corneal thinning (SLT), contact lens use (CL), and central corneal thickness (CCT) in all age groups. Additionally, the anterior chamber volume (ACV) and keratoconus match index (KMI) were associated with progression in age group 1. Location of the thinnest corneal thickness at the vertical axis (TCTy), distance from apex to the thinnest point (BADISTAPEX), scissor reflection in retinoscopy (SKIAREFLEX), and Vogt striae were associated with progression in age group 2, and TCTy, anterior and posterior asphericity (ASPA and ASPP, respectively), BADISTAPEX, SKIAREFLEX, and Vogt striae were associated with progression in age group 3. The multivariate model with the highest predictability indicated RVP, ACV, and SLT as independent determinants of progression in age group 1 (AUC: 90%, sensitivity: 88.9%, specificity: 90.9%), RVP, ACV, SLT, and SKIAREFLEX in group 2 (AUC: 81.6%, sensitivity 88.5%, specificity: 70.3%), and RVP, SLT, Vogt striae, and CL in age group 3 (AUC: 80%, sensitivity 82.8%, specificity: 73%).Conclusion ACV and KMI seem to play a major role in the progression of pediatric KC compared to adults. This is probably due to different anatomical and biomechanical characteristics of a childʼs eye globe.
Keywords: keratoconus; progression; adults; risk factors; pediatric